Code Switching in Critical Eleven Novel - Wiruma Titian Adi (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2018)
The objectives of this research are to find the types of code switching used in the novel and to describe the reasons influencing the use of code switching in the novel. This research used descriptive qualitative method; this method used to describe clearly about the fact of code switching weather the form and the reasons based on the data that gained through reading the whole contain of the novel. Analysis focused on three types of code swtiching (inter-sentential switching, intra-sentential switching and tag-switching) and the reasons of code switching. The results of the analysis revealed that mostly inter-sentential switching of utterance used in this novel.